\
"We compute as follows:"
lim_{x rarr 0} ( ( a + x )^a / a^{a +x} )^{1/x} \ = \ lim_{x rarr 0} ( 1/ a^x )^{1/x} \cdot ( ( a + x )^a / a^{a} )^{1/x}
\qquad \qquad \qquad \qquad \qquad \qquad \qquad \qquad \qquad = \ lim_{x rarr 0} 1/ a \cdot ( ( { a + x }/a )^a)^{1/x}
\qquad \qquad \qquad \qquad \qquad \qquad \qquad \qquad \qquad = \ lim_{x rarr 0} 1/ a \cdot ( ( 1 + x/a )^a)^{1/x}
\qquad \qquad \qquad \qquad \qquad \qquad \qquad \qquad \qquad = \ lim_{x rarr 0} 1/ a \cdot ( 1 + x/a )^{a/x}
\qquad \qquad \qquad \qquad \qquad \qquad \qquad \qquad \qquad = 1/ a \cdot e
\qquad \qquad \qquad \qquad \qquad \qquad \qquad \qquad \qquad = e / a.
\
"Thus:"
\qquad \qquad \qquad \qquad \qquad \qquad \quad \ lim_{x rarr 0} ( ( a + x )^a / a^{a +x} )^{1/x} \ = \ e / a.
\
"In the case of this problem:" \quad a = 1 + \sqrt{2}.
\qquad \qquad \qquad \qquad \qquad :. \qquad \quad \ lim_{x rarr 0} ( ( a + x )^a / a^{a +x} )^{1/x} \ = \ e / { 1 + \sqrt{2} }.